Efficiency and stability: A comparative study between islamic and conventional banks in GCC countries - Md. Dulal Miah; Helal Uddin (Future Business Journal, 2017)
This research aims at examining the differences between Islamic and conventional banks in terms of business orientation, stability, and efficiency. Data for this research are collected from 48 conventional banks and 28 Islamic banks of the Gulf Cooperative Council (GCC) countries over the period 2005 to 2014. Collected data are analyzed using accounting ratios, Stochastic Frontier Analysis (SFA), and ordinary least square (OLS) regression technique. Results show that conventional banks are more efficient in managing cost than their Islamic counterparts. However, Islamic banks are more solid in terms of short-term solvency but no such difference exists as far as the long-term stability is concerned. Regression estimation further shows that the operations of Islamic banks are different from their conventional counterparts and the results remain statistically significant even after controlling for bank specific variables. Moreover, larger banks have less intermediation ratio which indicates diseconomies of scale. Results also indicate that highly capitalized banks are more stable but cost inefficient which proves that capital-rich banks have failed to capitalize on the leverage effect.
Keywords: G21; G28; 650; Cost efficiency; Financial crisis; Financial stability; GCC; Islamic banks